Study on quality of wastewater from car wash premises - Izzati Syazwani bt Ahmad Tal'at (School of Materials Engineering, University Malaysia Perlis, 2011)
Car wash wastewater (CWW) normally contains oil and grease, rubber, paints, phosphate, dust and sand and organic matter. The wastewater runoff from the car enters the gutters gone into the storm water system. The wastewater from storm water does not undergo treatment before it is discharge, any pollutants in storm pollutants end up in our rivers and sea. The objective of this research is to study the wastewater quality produced from car wash premises. Therefore, ideal solutions can be suggested to overcome the problem with the simple wastewater treatment such as aeration and adding alum. Three car wash premises were selected in area Perlis for this study. The wastewater sample was taken from the site at two points such as car washing area and discharge outlet. These samples will undergo pH, Total Suspended Solid (TSS), Phosphate and Chemical Oxygen Demand (COD) tests in the laboratory. There are some parameters such as pH, TSS and Phosphate did not show any significant result on wastewater. But after looking at other parameters such as COD, the wastewater from car wash premises shows COD values a from the car wash premises is at the range 78 mg/l to 564 mg/L. Based on the test results, the wastewater produced by the car wash premises seems to bring hazardous to the environment after tests with several parameters. Then, after overcome this problem with the treatment process the total COD reduction after combined effect of aeration and alum treatment around 70% to 90%.